2020
DOI: 10.1111/nmo.13858
|View full text |Cite
|
Sign up to set email alerts
|

Purgative/laxative actions of Globularia alypum aqueous extract on gastrointestinal‐physiological function and against loperamide‐induced constipation coupled to oxidative stress and inflammation in rats

Abstract: Background Chronic constipation is a gastrointestinal functional disorder which affects patient quality of life. Therefore, many studies were oriented to search herbal laxative agents. In this study, we investigated the effect of Globularia alypum L. leaves aqueous extract (GAAE) against loperamide (LOP)‐produced constipation. Methods Animals were given LOP (3 mg/kg, b.w., i.p.) and GAAE (100, 200, and 400 mg/kg, b.w., p.o.) or yohimbine (2 mg/kg, b.w., i.p.), simultaneously, for 1 week. Gastric‐emptying test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Therefore, reducing oxidative stress-induced ICCs apoptosis may be a therapeutic target for STC. MDA is a biomarker of oxidative stress, and GSH-Px is an important reactive oxygen species scavenging enzyme that maintains redox balance in the body ( Hajji et al, 2020 ). According to our results, in the STC group, the MDA content increased, while the GSH-Px activity decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing oxidative stress-induced ICCs apoptosis may be a therapeutic target for STC. MDA is a biomarker of oxidative stress, and GSH-Px is an important reactive oxygen species scavenging enzyme that maintains redox balance in the body ( Hajji et al, 2020 ). According to our results, in the STC group, the MDA content increased, while the GSH-Px activity decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The studies suggested that loperamide could inhibit intestinal motility and intestinal fluid secretion through several mechanisms such as blocking acetylcholine release [ 18 ] and calcium channels [ 19 ], as well as inhibiting the function of calmodulin [ 20 ]. Thus, loperamide is extensively used to establish animal constipation models [ 21 23 ]. In the present study, we successfully established a constipation rat model using loperamide treatment, as evidenced by decreases in fecal pellets, fecal water content, and intestinal transit rate.…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences of diarrhea is the softening of stools or an increase in the number of watery stools together with abdominal cramps 1‐40 . Castor oil has been a useful experimental tool in the search for antidiarrheal preparations 41 given that it is hydrolyzed in the duodenum by pancreatic enzymes, leading to the release of ricinoleic acid that promotes alteration of electrolytes permeability on the intestinal mucosa increasing peristaltic activity 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Some plants have shown therapeutic potential in the treatment of gastrointestinal diseases, 7‐9 and studies have shown that secondary metabolites may be responsible for normalizing intestinal transit 10,11 or treat intestinal disorders 12 . Given the therapeutic potential, plants such as lemon balm ( Lippia alba Mill) and guava ( Psidium guajava L., Myrtaceae) are used to treat digestive, hepatic, diarrheal, and dysenteric disorders 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation